Persepsi Guru Pendidikan Agama Islam Tentang Kebijakan Merdeka Belajar Di Madrasah Tsanawiyah Ykui Sekargadung Dukun Gresik - Jamilatussholikhah; Noor Amirudin; Ode Moh. Man Arfa Ladamay (STIT Muhammadiyah Paciran, 2022)
The different perceptions given by the community, especially educators about the implementation of the independent learning policy make researchers want to raise and find out the problem in one of the educational institutions located at MTs YKUI Sekargadung Dukun Gresik. This study aims to determine the perception of PAI teachers regarding the policy. This study uses a qualitative approach which aims to be able to find out about how the description of objects that have been studied systematically, whether it is about facts, characteristics or various things related to the research theme. Data collection techniques are carried out by means of observation, interviews, and documentation. While the data analysis technique is by means of reduction, display, and verification. The results of this study are teachers at MTs YKUI Sekargadung have different and positive perceptions about the Kemendikbud Nadiem Makarim's policy of independent learning.